Health Information Systems Training for a Countrywide Implementation in Uruguay - Margolis, A.; Vero, A.; Bessonart, L.; Barbiel, A.; Ferla, M. (Yearbook of Medical Informatics, 2009)
Objectives Health Information systems training is one of the bottlenecks in clinical systems implementation. In this article, a strategy to massively create and train interdisciplinary coordinating teams is described for a project in Uruguay at FEMI, a non-academic setting which includes 23 health care institutions across the country and a tertiary referral center in Montevideo.Methods A series of educational activities were designed for the local coordinating teams. They included both onsite and online formats, site visits, integrated with some of the project tasks.Results In total, 128 professionals from all the Institutions participated in one or more of the training sessions (onsite and online) and 87 of them accomplished one of the forms of training.Conclusions Massive basic health informatics training was possible in Uruguay through collaboration with academic institutions at the country and regional level. Next steps include an active involvement of nurses in the educational events and planning of massive training of end users.
Keywords: Uruguay; South America; information systems; inservice training